Biocontrol of Pseudomonas Aeruginosa Biofilm Using Bacteriophages - Zahraa J. Jameel (Journal of Global Pharma Technology, 2016)
inanimate surfaces. Clinically, it is considered essential in the practical therapy. In current study, the inhibition effect of bacteriophages against biofilm of P. aeruginosa detected by ELISA method had been assessed. 50 samples had been collected from wounds infections in General Baqubah Hospital to isolate Pseudomonas aeruginosa and tested for 10 groups of antibiotics.  Befor the treatment, Pseudophage was isolated from sewage water of General Baqubah Hospital through pseudophage enrichment. The biocontrol of biofilm activity of pseudophage was applied by using the ELISA method. For the 50 samples were collected from wounds infections, and 10 isolates only were able to grow on Pseudomonas and Cetrimide agar. P. aeruginosa isolates showed high resistance associated with Cefepime (30 μg), Fusidic acid (10 μg) and Ampicillin (10 μg) 9(90%) while P. aeruginosa isolates showed high resistance associated with Erythromycin 80% then Imipenem and Tetracycline 70%. All 10 P. aeruginosa isolates have the production of biofilm. 4 P. aeruginosa bacteriophages (Pab 1, Pab 2, Pab 3, Pab 4) were isolated from sewage water, the Pab4 had a wide range. P. aeruginosa were sensitive to pseudophage by spotting assay were inhibited the biofilm formation. Active effect of pseudophage to inhibit Pseudomonas aeruginosa' biofilm in vitro.